Ion-Photon Spectrometry Study of the Organic Dye−Lipid System - Alimov, S.S.; Afanas’eva, I.A.; Bobkov, V.V.; Gokov, S.P.; Gritsyna, V.V.; Shevchenko, D.I. (Ukrainian Journal of Physics, 2022)
The spectral composition, quantum yield, and spatial distribution of excited particles emitted from the surface of the organic dye-lipid system bombarded with argon ions have been studied. The presence of lipids in a target was found to change the number of excited particles emitted from the surface in comparison with the case of pure dye. On the basis of the data obtained, a mechanism of influence of lipids on the excited particle yield has been proposed.